2003
DOI: 10.1074/jbc.m309115200
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1, a Cell-Cell Adhesion Molecule, Directly Associates with Annexin II in a Three-dimensional Model of Mammary Morphogenesis

Abstract: The epithelial cell adhesion molecule CEACAM1 (carcinoembryonic antigen cell adhesion molecule-1) is down-regulated in colon, prostate, breast, and liver cancer. Here we show that CEACAM1-4S, a splice form with four Ig-like ectodomains and a short cytoplasmic domain (14 amino acids), directly associates with annexin II, a lipid raft-associated molecule, which is also downregulated in many cancers. Annexin II was identified using a glutathione S-transferase pull-down assay in which the cytoplasmic domain of CEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 81 publications
1
34
1
Order By: Relevance
“…This function of AII has been suggested in fibrinolysis and anti-angiogenesis (Kwon et al 2002;Macleod et al 2003;Ling et al 2004). Binding of AII to the membrane surface has been implicated in cell-cell adhesion (Tressler et al 1993;Chung and Erickson 1994;Kirshner et al 2003).…”
Section: Annexin-ii (Aii) Is a Camentioning
confidence: 99%
“…This function of AII has been suggested in fibrinolysis and anti-angiogenesis (Kwon et al 2002;Macleod et al 2003;Ling et al 2004). Binding of AII to the membrane surface has been implicated in cell-cell adhesion (Tressler et al 1993;Chung and Erickson 1994;Kirshner et al 2003).…”
Section: Annexin-ii (Aii) Is a Camentioning
confidence: 99%
“…Both associate with rafts and appear to mediate interaction with the cytoskeleton (Babiychuk and Draeger, 2000;Draeger et al, 2003). Other structures providing examples of recruitment of annexins to actinassociated membrane areas are (i) endothelial adherens junctions, which recruit annexin A2, together with the Shp2 tyrosine phosphatase, in a cholesterol-dependent manner, (ii) epithelial adherens junctions, at which annexin A2 associates with Rac1-containing complexes and (iii) the adhesion molecule CEACAM (Burkart et al, 2003;Hansen et al, 2002;Kirshner et al, 2003). In polarizing epithelial cells, annexin A2 and its intracellular protein ligand S100A10 (see below) are targeted to actin-rich apical junctions, where they function in a complex with the large actin-binding protein AHNAK in organizing the cortical actin cytoskeleton during polarization (Benaud et al, 2004).…”
Section: Annexins As Membrane Scaffold Proteinsmentioning
confidence: 99%
“…However, both of these assays fail to mimic the in vivo situation where the cytoplasmic domain protrudes from the phospholipid membrane in an organized, oriented manner. To approximate these conditions, we have synthesized the CEACAM1 cytoplasmic domain peptide with an N-terminal MUA acyl group that permits oriented binding of the peptide to a biosensor gold surface (23), in solution as oriented micelles, or as described later, to a CM5 chip using thiol immobilization chemistry. As show in Fig.…”
Section: Binding Kinetics Of the Cytoplasmic Domain-actin Interactionmentioning
confidence: 99%
“…Because the cytoplasmic domain of this isoform is only 12-14 amino acids in length (the exact start of the domain is in doubt) it was originally thought not to play a role in signal transduction, but perhaps acted in a dominant negative fashion in the presence of the long cytoplasmic domain. However, we have shown that peptides or glutathione S-transferase fusion proteins from the short cytoplasmic domain bind directly to actin, tropomyosin, calmodulin, and more recently, to the annexin-2 p11 tetramer AIIt (21)(22)(23).…”
mentioning
confidence: 99%